2015
DOI: 10.1007/s00276-015-1485-9
|View full text |Cite
|
Sign up to set email alerts
|

Arterial supply to the soleus muscle: an anatomical study with emphasis on its application in the pedicle flap surgery

Abstract: The present study has provided additional information on the various patterns in the extra muscular part of arterial supply to the soleus muscle. This knowledge is important to the plastic and orthopedic surgeons while performing the pedicle flap surgeries. Our opinion is that the proximally based soleal muscle flaps are more beneficial in the surgical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Owing to the less bulkiness, the medial Hemi-soleus muscle ap is cosmetically superior to the full soleus muscle ap, which happens to be bulkier. 4,10,11 In this study, all the flaps survived. Ahmad I et al 8 in their series of 40 cases, reported a complete loss of two flaps.…”
Section: Discussionmentioning
confidence: 70%
“…Owing to the less bulkiness, the medial Hemi-soleus muscle ap is cosmetically superior to the full soleus muscle ap, which happens to be bulkier. 4,10,11 In this study, all the flaps survived. Ahmad I et al 8 in their series of 40 cases, reported a complete loss of two flaps.…”
Section: Discussionmentioning
confidence: 70%
“…However, a surprising finding was that gastrocnemius necrosis was not the risk factor for poor ankle function in our series. This can be explained by the compensatory results of soleus and plantar flexor muscles and the patients' low demand for ankle function [ 32 ]. In fact, there is no existing evidence about whether gastrocnemius artery repair contributes to lower functional outcomes in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Distally, the minor pedicles are located between 6–7 cm and 11–13 cm proximal to the medial malleolus [8] . Prathapamchandra et al [9] studied 38 adults lower limbs and found that the mean distance of the last pedicle of a posterior tibial artery that supplies the distal part of medial hemisoleus is 29.9 ± 4.7 cm from the imaginary horizontal line that crosses the head of the fibula at the level of the most proximal attachment of soleus muscle, with the range of 20.1–37.5 cm. Some anatomical variations do exist.…”
Section: Discussionmentioning
confidence: 99%